Assessing the stability of a protective soil-cement structure in the soil massif under the action of critical explosive impacts - Remez, Natalia; Haiko, Hennadii; Bronytskyi, Vadym; Hrebeniuk, Tetiana; Haiko, Svitlana (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates dynamic interaction between the soil and an obstacle under explosive loading. The task addressed is to protect underground structures with shallow laying in the soil massif from the effect of critical explosive influences, which is becoming increasingly relevant under conditions of military threats. A methodology has been devised to numerically solve the problem of a cylindrical warhead explosion on the surface of the soil massif, taking into account the interaction with the foundation-cement obstacle. That has made it possible to investigate the patterns of change in wave processes in the soil and obstacle depending on time, charge mass, and depth of the screen. The wave interaction between the explosion and the soil massif with an obstacle was numerically simulated. The isobar field was determined at different times and velocity isoseisms were defined, which show the dynamics of wave propagation deep into the soil massif and changes in their velocity. Dependences of the peak stress on the depth for different warhead masses (50, 150, and 500 kg) were derived, as well as the resulting peak stresses and the minimum safe horizontal distances to the epicenter of the explosion for the obstacle. The dependences between the deflection and pressure of the protective soil-cement structure were determined, which makes it possible to predict the stability of the protective screen at its different thickness. It has been established that the peak stress decreases rapidly with distance from the epicenter of the explosion. For R < 3.7 m, the screen (obstacle) is in the zone of high tensile stresses (σmax > 2 MPa), which leads to crushing, loss of shape, and stability of the structure. For R ≈ 7.4 m, the tensile stress decreases to approximately 0.3–0.5 MPa. These values should be considered as a threshold value for maintaining the holding (protective) function of the soil-cement obstacle. A nomogram has been constructed to assess the mechanical properties of a soil-cement barrier located at a certain depth during a surface explosion of a warhead of different mass depending on the cement content. This facilitates practical management of the stability of the protective structure by adjusting the parameters of the bonding mixture. The prospects of engineering protection of underground facilities by forming a continuous soil-cement screen in the path of the blast wave, formed by jet cementing of soils, have been proven